Bacteriochlorophyll and Heme Synthesis in Rhodopseudomonas spheroides: Possible Role of Heme in Regulation of the Branched Biosynthetic Pathway - Lascelles, June (1969)
Synthesis of heme, measured by incorporation of iron-59, and of bacteriochlorophyll was studied with wild-type and mutant strains of Rhodopseudomonas spheroides. The wild type formed heme from glycine and succinate at one-fortieth the rate of bacteriochlorophyll under anaerobic-light conditions. Added δ-aminolevulinate stimulated heme synthesis 10-fold without increasing bacteriochlorophyll production. Heme synthesis from glycine and succinate was increased when the magnesium branch of the biosynthetic path was curtailed by mutation or by p-fluorophenylalanine or 8-azaguanine. Synthesis of bacteriochlorophyll by the wild type from glycine and succinate stopped immediately after addition of puromycin, but heme production continued for a period. Porphyrins and other precursors did not appear upon addition of puromycin alone, but simultaneous addition of o-phenanthroline resulted in the accumulation of coproporphyrin. Production of this porphyrin by a mutant strain with impaired ability to form heme was unaffected by puromycin. Heme synthesis from glycine and succinate or from δ-aminolevulinate was decreased by limitation of methionine; it is suggested that coproporphyrin accumulation from glycine and succinate under conditions of methionine deficiency results from relief of feedback inhibition of δ-aminolevulinate synthase by heme. The development of δ-aminolevulinate synthase activity in response to low aeration is prevented by addition of δ-aminolevulinate. This repressive action of the latter is abolished when its conversion to heme is impeded by mutation or by methionine deficiency. It is suggested that heme, the quantitatively minor end product of the branched biosynthetic pathway, may regulate the flow of common intermediates when utilization of protoporphyrin by the magnesium branch is diminished. This regulation may be exerted by feedback inhibition of δ-aminolevulinate synthase and also by repression of enzyme formation.